Phytochemical characterization and antihyperglycemic activity of kemumu (Colocasia gigantea Hook. f.) leaf stalk juice in glucose-loaded mice (Mus musculus L.) - Reni Kurniati; Nur Azizah Muhti’ah; Retno Aryani; Rudy Agung Nugroho; Ratna Kusuma; Lariman Lariman; Annisa Nurul Ilmi (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Kemumu leaf stalk juice (Colocasia gigantea Hook. f.) is traditionally used to control blood sugar levels. However, scientific evidence is still limited and further studies are required for this purpose. This study aims to analyze the phytochemical content and test the ability of kemumu leaf stalk juice to reduce blood sugar levels in glucose-loaded mice. Secondary metabolites examined included tannins, alkaloids, phenolics, saponins, steroids, triterpenoids, and flavonoids. The antihyperglycemic activity was evaluated using 20 adult male mice (Mus musculus L.) as an animal model. First, fasting blood sugar levels were measured, then the mice were given 50% glucose. After 30 minutes, blood sugar levels were measured again. The mice were divided into 5 groups: 2 control groups and 3 treatment groups. The negative control group mice received 0.2 ml of distilled water, and the positive control group mice received glibenclamide at 0.65 mg/kg BW. Mice in treatment groups 1, 2, and 3 were given 0.05 ml/20 g BW, 0.1 ml/20 g BW, and 0.2 ml/20 g BW of kemumu juice, respectively. Blood sugar levels were measured every 30 minutes for up to 180 minutes. Data were analyzed using ANOVA, and if significant differences were found, an LSD test was performed. The results showed that kemumu juice contains alkaloids, phenolics, and flavonoids, which have antidiabetic properties. Doses of 0.1–0.2 ml were as effective as glibenclamide in the positive control group.